PURCHASE SYSTEM ANALYSIS ON FOOD COST IN HILTON GARDEN INN BALI - I Putu Gede Cita Setiawan; I Ketut Astawa; I Gusti Putu Sutarma (Journal of Applied Sciences in Travel and Hospitality, 2018)
This study was conducted at the culinary department at Hilton Garden Inn Bali where in production activities often experience shortage of materials caused by the reception of stranded guest, this is due to the location of Hilton Garden Inn Bali located near with airport, resulting in a significant increase in the number of occupancy rooms followed by an increase in demand procurement of food, thereby increasing the chances of shortage of production materials in the culinary department. This study focuses on the analysis of the application of goods purchasing system for the operational activities of the culinary department to meet the needs of the production, and the effect of applying the procurement system to the food cost position. The objective of this research is to measure how big the influence of the application of procurement system of material needs to the position of food cost, in the event of stranded with large amount. In this study using quantitative descriptive analysis method and the results of this study found that the purchase system has a great influence where in the case study the procurement of production materials can meet the demand but the oprasional system applied is not running properly.